2015
DOI: 10.1021/jacs.5b10592
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Molecular Function of Human BOLA2 in GRX3-Dependent Anamorsin Maturation Pathway

Abstract: In eukaryotes, the interaction between members of the monothiol glutaredoxin family and members of the BolA-like protein family has been involved in iron metabolism. To investigate the still unknown functional role of the interaction between human glutaredoxin-3 (GRX3) and its protein partner BOLA2, we characterized at the atomic level the interaction of apo BOLA2 with the apo and holo states of GRX3 and studied the role of BOLA2 in the GRX3-dependent anamorsin maturation pathway. From these studies, it emerge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
87
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(92 citation statements)
references
References 48 publications
5
87
0
Order By: Relevance
“…Several studies in yeast have underscored the critical role of cytosolic monothiol glutaredoxins and their BolA-binding partners in iron homeostasis (26,33,48), and a recent in vitro study of human Glrx3 and BolA2 characterized their capacity to bind and transfer [2Fe-2S] clusters (14,27). Here, we show that Glrx3 and BolA2 form a complex in human cells and that complex formation is highly dependent on coordination of bridging Fe-S clusters.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Several studies in yeast have underscored the critical role of cytosolic monothiol glutaredoxins and their BolA-binding partners in iron homeostasis (26,33,48), and a recent in vitro study of human Glrx3 and BolA2 characterized their capacity to bind and transfer [2Fe-2S] clusters (14,27). Here, we show that Glrx3 and BolA2 form a complex in human cells and that complex formation is highly dependent on coordination of bridging Fe-S clusters.…”
Section: Discussionmentioning
confidence: 52%
“…(43,47). In vitro work also demonstrates the transfer of [2Fe-2S] clusters from Glrx3 homodimers and Glrx3⅐BolA2 complexes to Ciapin1 (27,28). These studies raise the possibility that [2Fe-2S] cluster exchange could occur between Ciapin1, Glrx3, and BolA2 in mammalian cells.…”
Section: Figure 6 Ciao1 Binds Glrx3 But Is Not Required For Glrx3⅐bomentioning
confidence: 79%
See 1 more Smart Citation
“…The assembly of Fe-S clusters onto Dre2 was reported to be independent of CIA components, a mechanism referred to as "unprecedented for a non-scaffold Fe-S protein" (Netz et al, 2010). Studies by Banci et al have recently elucidated not one, but two alternative maturation pathways for Dre2 in the cytosol (Banci et al, 2015a(Banci et al, , 2015b.…”
Section: Fe-s Assembly Machineriesmentioning
confidence: 99%
“…GRX3 is an in vivo Dre2 binding partner in both yeast (Rual et al, 2005) and mouse in the cytosol. A specific interaction between the N-terminal domains of the two proteins promotes the transfer of two 2Fe-2S clusters from GRX3 (Banci et al, 2015b) or GRX3-BOLA2 (Banci et al, 2015a) to Dre2. It was suggested that these two pathways may be operative under normal and oxidative stress conditions, respectively (Banci et al, 2015a).…”
Section: Fe-s Assembly Machineriesmentioning
confidence: 99%